Introducing an agricultural app to urban vegetable farmers: a pilot study in Hanoi - Bui, Trang; Nguyen, T.T.L.; Nguyen, T.S.; Kawarazuka, Nozomi; Schreinemachers, Pepijn; Liu, Yanyan (International Potato Center, 2022)
Plantix is an agricultural app which offers diagnosis and advice for more than 30 crops. It was developed by a private company based in Germany. It has a great potential as a new form of extension service complementing a traditional face-to-face extension service. CGIAR’s Plant Health Initiative seeks to introduce the app as part of a package of innovations available for integrated pest and disease management to facilitate farmers’ behavioral change. Plantix has been widely used in India, but it has not been very common yet in Vietnam. The aim of this pilot study is to test the usability of Plantix app for urban vegetable growers in Hanoi, Vietnam. 12 farmers (6 women and 6 men) participated in the training on how to use the app and provided feedback after a two-week trial. Results show that both women and men farmers are greatly interested in using the app. Some farmers purchased and sprayed appropriate pesticides following advice from the app. Each participant shared the app with 2-5 relatives, friends and/or neighbors. Women shared the app with their husbands as well as their female peers, while men tended to share it with their male peers. Although this pilot study confirms the usability of the app in the urban context of Vietnam with few constraints in access to internet and digital literacy for both women and men, some adjustments are required to meet their needs and to fit with the context.